2016
DOI: 10.1212/wnl.0000000000002307
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection as a risk factor for Parkinson disease

Abstract: We conducted a large nationwide population-based study and found that patients with HCV exhibit a significantly increased risk of developing PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 28 publications
0
44
1
Order By: Relevance
“…A total of 6,609 possibly relevant articles were identified in PubMed and EMBASE database by our search strategy and manual searching; no relevant article published in Chinese was identified in CNKI database. As shown in Figure 1, 23 observational studies (Arsic Arsenijevic et al, 2014;Blaecher et al, 2013;Bu et al, 2015;Charlett et al, 1999Charlett et al, , 2009Dobbs, Charlett, Dobbs, Weller, & Peterson, 2000;Golabi et al, 2017;Goldstein, Fogel-Grinvald, & Steiner, 2019;Harris et al, 2012;Hemling et al, 2003;Huang et al, 2018;Kim et al, 2016;Nafisah et al, 2013;Nielsen, Qiu, Friis, Wermuth, & Ritz, 2012;Pakpoor et al, 2017;Sasco & Paffenbarger, 1985;Su et al, 2019;Tanner et al, 2012;Toovey, Jick, & Meier, 2011;Tsai et al, 2016;Tsolaki, Kountouras, Topouzis, & Tsolaki, 2015;Vlajinac et al, 2013;Wu et al, 2015) including six retrospective cohort study and 17 case-control studies published from 1965 to 2019 were included. Among these 23 studies, infection of 21 pathogenic microorganisms including eight bacteria, 12 viruses and one fungus were reported (Table 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…A total of 6,609 possibly relevant articles were identified in PubMed and EMBASE database by our search strategy and manual searching; no relevant article published in Chinese was identified in CNKI database. As shown in Figure 1, 23 observational studies (Arsic Arsenijevic et al, 2014;Blaecher et al, 2013;Bu et al, 2015;Charlett et al, 1999Charlett et al, , 2009Dobbs, Charlett, Dobbs, Weller, & Peterson, 2000;Golabi et al, 2017;Goldstein, Fogel-Grinvald, & Steiner, 2019;Harris et al, 2012;Hemling et al, 2003;Huang et al, 2018;Kim et al, 2016;Nafisah et al, 2013;Nielsen, Qiu, Friis, Wermuth, & Ritz, 2012;Pakpoor et al, 2017;Sasco & Paffenbarger, 1985;Su et al, 2019;Tanner et al, 2012;Toovey, Jick, & Meier, 2011;Tsai et al, 2016;Tsolaki, Kountouras, Topouzis, & Tsolaki, 2015;Vlajinac et al, 2013;Wu et al, 2015) including six retrospective cohort study and 17 case-control studies published from 1965 to 2019 were included. Among these 23 studies, infection of 21 pathogenic microorganisms including eight bacteria, 12 viruses and one fungus were reported (Table 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…A number of epidemiological studies have reported an increased risk of PD risk following various types of infections and inflammation, including hepatitis C, herpes viruses, influenza, and H. pylori . Interestingly, both vagotomy studies reported an increased PD risk (HR = ∼1.1‐1.2) among the selective/super‐selective vagotomy patients compared to the background population.…”
Section: Protective Effect Of Vagotomymentioning
confidence: 99%
“…90 Findings from studies in the East have shown an association between only Hepatitis C infection and PD; whereas one retrospective cohort study from the UK found an association between the Hepatitis B and C virus infection with PD, but not with other forms of hepatitis. 91 Large nationwide health-insurance database and large regional screening programs for Hepatitis, implemented in Taiwan, have enabled this previously unknown association between the Hepatitis C virus and PD to be described, 92 findings of which have been recently replicated in the West in a nationwide UK study, utiliaing the UK HES database. 93 Mechanisms proposed for the association include, direct Hepatitis C virus infection of the brain and interferon induced Parkinsonism.…”
Section: Hepatitis Cmentioning
confidence: 99%